Legal Updates on the Prevention and Handling System for Child Victims of Exposure to Digital Radicalism through Social Media and Online Games from a Child Protection Perspective - Fani Asiah Pratidina; Vita Mayastinasari; Kif Aminanto (Indonesian Journal Publisher, 2026)
The development of social media and online games has transformed the pattern of radicalism, spreading from conventional methods to digital radicalism, which is more hidden, interactive, and difficult to monitor by conventional legal systems. Children are a vulnerable group to exposure to radical ideology due to the high intensity of digital space use, weak digital literacy, and the influence of social media algorithms and online game virtual communities that form echo chambers and soft radicalization. This study aims to analyze the legal problems in preventing and handling child victims of exposure to digital radicalism through social media and online games, and to formulate an ideal legal reconstruction and reform from the perspective of child protection in Indonesia. This study employs a normative juridical method with statutory and conceptual approaches through an analysis of various regulations related to child protection, cyber law, and the eradication of terrorism. The results show that the Indonesian legal system is still partial and does not have specific regulations regarding the protection of children from exposure to digital radicalism, including weak supervision of digital platforms, the absence of a national early detection system, and the dominance of a repressive approach in handling children exposed to radicalism. Therefore, legal reform is needed through reformulating digital-based child protection regulations, strengthening the legal responsibility of social media and online gaming platforms, establishing a national digital early warning system, harmonizing child protection laws with cyber and criminal law, and developing a child-specific deradicalization model based on psychological rehabilitation and social reintegration. These legal reforms are expected to build a child protection system that is preventive, rehabilitative, humane, and responsive to developments in digital technology in Indonesia.